Numerical study to enhance the heat transfer using sinusoidal wavy surface for turbulent wall jet - Singh T.P.; Kumar A.; Satapathy A.K. (My University, 2025)
To achieve higher heat transfer rate for cooling by air jet impingement is the most essential goal of the modern era. The aim of this article is to enhance the heat transfer rate significantly by using the sinusoidal wavy surface in a turbulent wall jet. A comprehensive numerical study is carried out to examine the complex behavior of turbulent wall jet flowing tangentially to the wavy surface. To explore all the possibilities associated with the wavy surface, the various number of cycles and amplitudes are considered; the number of cycle (n) is varied between 4 and 12 and the amplitude (A) is changed from 0.1 to 0.7. The results indicate that the local Nusselt number, local heat flux and Umax increase near the exit of the nozzle, while Pmin decreases when the amplitude of the wavy surface increases. Although these parameters increase near the jet exit; but the fate of these parameters are highly dependent on the number of cycle (n) and the amplitude of the wavy surface (A) in the downstream direction. Accordingly, a maximum increase of 14.43% of heat transfer rate is observed for n = 7 and A = 0.7. Also, the self-similar behavior shows different trends as compared to the plane wall case which is discussed in detail. © 2019, © 2019 Taylor & Francis Group, LLC.